'One of These Days I'm Gonna Pay it Back': Debt Collection Practices in New Zealand – What New Research has Revealed - Stace, Victoria; Bentley, Maisy; Malloch, Hanna (Victoria University of Wellington Law Review, 2022)
Recent research conducted by Victoria University of Wellington provides evidence of debt collection practices in New Zealand. This article discusses the findings of the research and makes recommendations to assist in addressing issues around harassment, use of attachment orders and accumulation of interest on old debts.